FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Dharpamahe, Arnavad; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2025)
This study aimed to find how the influence of profitability, corporate finance and firm size on dividend policy in manufacturing companies consumer non-cylicals and healthcare sector were listed on Indonesia Stock Exchange for 2019-2021. The sample was selected using purposive sampling method with the final sample data of 30 companies. The data processing technique used multiple linear regression analysis assisted by the SPSS Version 29.0 program and Microsoft Excel 2016. The results of this study indicated that profitability had significant positive effect on dividend policy. Meanwhile, corporate finance and firm size have no significant positive effect on dividend policy.